2020
DOI: 10.1038/s41598-020-77140-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma imatinib levels and ABCB1 polymorphism influences early molecular response and failure-free survival in newly diagnosed chronic phase CML patients

Abstract: Achieving early molecular response (EMR) has been shown to be associated with better event free survival in patients with chronic phase chronic myeloid leukemia (CP-CML) on Imatinib therapy. We prospectively evaluated the factors influencing the 2-year failure free survival (FFS) and EMR to imatinib therapy in these patients including day29 plasma Imatinib levels, genetic variants and the gene expression of target genes in imatinib transport and biotransformation. Patients with low and intermediate Sokal score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…ABCB1 is one of the most well-established ABC transporters that mediates MDR in cancer cells. To dates, a wide range of anticancer drugs were iden-tified as substrates of ABCB1, including chemotherapeutic agents doxorubicin, paclitaxel, vincristine 57 , and tyrosine kinase inhibitors GSK1070916 58 , WYE354 59 , imatinib 60 . suggesting the anticancer effect may be attenuated in ABCB1-overexpressing cancer cells.…”
Section: Abcb Subfamilymentioning
confidence: 99%
“…ABCB1 is one of the most well-established ABC transporters that mediates MDR in cancer cells. To dates, a wide range of anticancer drugs were iden-tified as substrates of ABCB1, including chemotherapeutic agents doxorubicin, paclitaxel, vincristine 57 , and tyrosine kinase inhibitors GSK1070916 58 , WYE354 59 , imatinib 60 . suggesting the anticancer effect may be attenuated in ABCB1-overexpressing cancer cells.…”
Section: Abcb Subfamilymentioning
confidence: 99%
“…After screening the titles and abstracts of articles, 47 studies were excluded because they were deemed repetitive or unqualified. After reading 28 potentially eligible papers, six studies from the literature met our inclusion criteria [ 14 , 15 , 16 , 17 , 18 , 19 ]. The study by Rajamani et al did not report imatinib plasma C trough for individual genotypes, but the authors provided the data on our request [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…After reading 28 potentially eligible papers, six studies from the literature met our inclusion criteria [ 14 , 15 , 16 , 17 , 18 , 19 ]. The study by Rajamani et al did not report imatinib plasma C trough for individual genotypes, but the authors provided the data on our request [ 14 ]. No additional studies were obtained by checking the reference lists of these articles.…”
Section: Resultsmentioning
confidence: 99%
“…TKI efficacy is highly dependent on cellular drug concentration to effectively block BCR-ABL activity, and low TKI concentrations have already been associated, at least in part, with reduced expression or activity of SLC transporters and/or increased expression or activity of ABC transporters [ 40 , 41 ]. The SNVs studied here, which are associated with altered expression and activity, have a potential role in response to therapy [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SNVs studied here, which are associated with altered expression and activity, have a potential role in response to therapy [ 42 , 43 ]. Recently Rajamani et al showed the influences of ABCB1 polymorphisms and plasma imatinib levels on early molecular response and failure-free survival [ 41 ]. Despite frequently having been associated with response by other authors [ 5 , 8 , 44 , 45 ], P-gP SNVs did not present a prognostic impact in our study.…”
Section: Discussionmentioning
confidence: 99%